2017
DOI: 10.1142/s2345748117500105
|View full text |Cite
|
Sign up to set email alerts
|

Co-movement and Forecasting Analysis of Major Real Estate Markets by Wavelet Coherence and Multiple Wavelet Coherence

Abstract: Wavelet coherence of time series provides valuable information about dynamic correlation and its impact on time scales. Here, the authors analyze the wavelet coherence of major real estate markets data, and take the USA, Hong Kong of China, Canada, Japan, and Developed Europe real estate market prices as time series. The wavelet coherence results show relationships among these markets, the correlations between the two and three markets (by multiple wavelet coherence) and how these relationships vary in the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Their findings suggest that the three markets of Greater China are integrated among each other and less integrated with the US markets, which can be justified by their closer economic ties and geographical closeness. Karatas et al (2017) used wavelet coherence test which confirmed the relationship among the real estate markets for USA, Hong Kong of China, Canada, Japan and developed Europe. Another research done by Chen et al (2020) used data from the Chinese as well as the American real estate market and found that the correlation between securities of China and America is negative in terms of their efficiency and complexity.…”
Section: Brief Literature Reviewmentioning
confidence: 97%
“…Their findings suggest that the three markets of Greater China are integrated among each other and less integrated with the US markets, which can be justified by their closer economic ties and geographical closeness. Karatas et al (2017) used wavelet coherence test which confirmed the relationship among the real estate markets for USA, Hong Kong of China, Canada, Japan and developed Europe. Another research done by Chen et al (2020) used data from the Chinese as well as the American real estate market and found that the correlation between securities of China and America is negative in terms of their efficiency and complexity.…”
Section: Brief Literature Reviewmentioning
confidence: 97%